(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2021)
Background: Outcome of TBM can be modified by several predictors. Objective: This study was undertaken to evaluate the predictors of outcome of tuberculous meningitis (TBM) at 6 and 9 months. Methodology: This hospital based prospective cohort study was carried out from October, 2016 to September, 2017 (1 year) in the in-patient Department of Neurology at the National Institute of Neurosciences & Hospital (NINS & H), Dhaka, Bangladesh. All the patients with age 18 years or more of both sexes with features of TBM fulfilling the case definition criteria was included as the study population. The outcome was measured at 6 and 9 months by modified Rankin Scale (mRS) with no disability (score=0-1), mild disability (score = 2), moderate disability (score=3-4), severe disability (score=5) and dead (score=6). For statistical analysis outcome was classified as death and survival group. A number of clinical, laboratory and radiological parameters were evaluated initially by univariate and finally multiple regression analysis. Results: A total 54 TBM patients were included in this study. Over 70% of the patients were adolescent or young adult (< 30 years) with mean age of 28.2 ± 12.3 years and 63% were female. Staging of the TBM showed that nearly half (48.1%) were at stage II and 37% cases were in stage III disease. Baseline imaging (CT-scan and MRI) showed basal meningeal enhancement in 40.7% cases, hydrocephalus in 40.7%, infarction 46.3% and tuberculoma in 29.6% cases. Final diagnosis was established as definite TBM in 3(5.6%) cases, probable TBM 30(55.6%) and possible TBM in 21(38.9%) cases. In terms of 6-months outcome, 16(29.6%) cases died and 10(18.5%) had recovered without any neurological sequelae; however, mild, moderate and severe disability were in11.1%, 27.8% and 13% cases respectively. At the 9 months of evaluation 13 (24.0%) had complete recovery without any neurological sequelae, 22 (40.9%) patients survived with various degree of disabilities like visual impairment, hemi or paraplegia, cognitive impairment, rests died giving a total mortality of 19(35.1%). In univariate analysis, age >50 years (p=0.019), duration of illness before initiation of treatment (>45 d) (p = 0.041), convulsion (p = 0.010), altered sensorium (p<0.001), delayed initiation of treatment >1 month (p=0.041) and stage III TBM (p<0.001) were significantly associated with mortality. In multivariate analyses stage III TBM (p=0.004), altered sensorium (p=0.036), delayed initiation of treatment >1 month (p=0.043) emerged as independent predictors of mortality. Conclusions: In conclusion stage III TBM, altered sensorium and delayed initiation of treatment more than 1 month are the independent predictors of mortality in TBM patients. Journal of National Institute of Neurosciences Bangladesh, January 2021, Vol. 7, No. 1, pp. 14-19